Improving Patient Safety and Reducing Medical Errors in Saudi Healthcare Organizations - Bokhari, Rasha Mohammadmaki (Journal of medical and pharmaceutical sciences, 2019)
This paper aimed to identify the critical areas that need improvement within the health care institutions’ systems in Saudi Arabia to enhance patient safety and reduce medical errors. Methodology: A systematic literature review was conducted to explore the moral issue of medical error and patient safety in the Saudi healthcare organizations system. Database yielded more than 4,000 candidate articles, of which 45 studies randomly selected after they fulfilled the inclusion criteria in this study. Results: The outcome of the research study was more than 45 articles that met the inclusion criteria and appeared to be highly relevant to the subject under investigation. The lack of the ethical responsibility to continuously improve the healthcare system, the lack of proper safety culture and active reporting system, and the lack of patient-centered care were documented as critical areas in Saudi healthcare organizations’ system in need of improvement to enhance patients’ safety and to reduce medical errors. Practical implication: the researcher made several recommendations based on what has been done in the United States’ healthcare system that systemically addresses improving patient safety and reducing medical errors. For instance, healthcare organizations devoted to improve patient safety and reduce medical error should abandon the routine assignment of individual blame and shift toward a system thinking approach. The devotion to enhancing patient safety stems from ethical responsibility and accountability of healthcare organizations toward the patients they serve. Also, healthcare organizations that lack a strong culture of safety will consequently not achieve a high level of patient safety. Finally, Healthcare organizations should pay attention to the essential role that patient involvement play in improving safety and reducing medical errors.